1996
DOI: 10.1677/joe.0.1480033
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonate 12-lipoxygenase in porcine anterior pituitary cells: its localization and possible function in gonadotrophs

Abstract: Arachidonate 12-lipoxygenase, which oxygenates positions 12 and 13 of arachidonic and linoleic acids, is present in porcine anterior pituitary cells. Colocalization of the 12-lipoxygenase with various pituitary hormones was examined by immunohistochemical double-staining using antibodies against 12-lipoxygenase and various anterior pituitary hormones. Under light microscopy, approximately 7% of the cells producing luteinizing hormone (LH) and follicle-stimulating hormone (FSH) were positive for 12-lipoxygenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In the tallow fed birds, a diet containing 25.8% w/w of LA (18:2n-6), the rise in circulating plasma GH concentrations fell between the two PUFA groups. Previous studies have shown that fatty acids from the n-6 series, specifically LA (18:2n-6), enhance the release of GHRH (Seflaris et al, 1992;Ikawa et al, 1996;Barb et al, 1997). In addition, Seflaris and co-workers (1992) have also shown an inhibitory effect of LA (18:2n-6) on the GH inhibiting factor, somatostatin, when cultured hypothalamic cells were exposed to oleic acid.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the tallow fed birds, a diet containing 25.8% w/w of LA (18:2n-6), the rise in circulating plasma GH concentrations fell between the two PUFA groups. Previous studies have shown that fatty acids from the n-6 series, specifically LA (18:2n-6), enhance the release of GHRH (Seflaris et al, 1992;Ikawa et al, 1996;Barb et al, 1997). In addition, Seflaris and co-workers (1992) have also shown an inhibitory effect of LA (18:2n-6) on the GH inhibiting factor, somatostatin, when cultured hypothalamic cells were exposed to oleic acid.…”
Section: Discussionmentioning
confidence: 98%
“…This finding may simply reflect the pulsatile LH secretory pattern, the lower LH concentrations a result of the sampling regimen particularly in respect to the pre-infusion period where only three basal sampling points were measured. However, it is also plausible that other factors may override the LH stimulatory nature of some fatty acids such as AA (20:4n-6) and oleic acid (Kennedy et al, 1994;Ikawa et al, 1996) and impinge on reproductive status. A possible candidate could be the hormone leptin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in porcine anterior pituitary cells the 12-lipoxygenase of the leukocyte-type was colocalized not only with gonadotrophin but also with other anterior pituitary hormones [8].…”
Section: Discussionmentioning
confidence: 99%
“…The biological significance of 12-lipoxygenase has not been fully understood [20] . Stimulatory effects of 12-lipoxygenase metabolites of arachidonic acid have been reported for various endocrine systems; LH-RH [3], melatonin [16], insulin [15], gonadotrophin [8] and aldosterone [11]. In addition, the presence of leukocytetype 12-lipoxygenase was demonstrated in various endocrine cells on biochemical, molecular biological and immunohistochemical bases: porcine anterior pituitary cells [19], rat pancreatic islet fl-cells [17], human adrenal glomerulosa cells [4] and rat pineal cells [5].…”
Section: Discussionmentioning
confidence: 99%